Living with fuel poverty in older age: Coping strategies and their problematic implications. (August 2016) - Chard, Rose; Walker, Gordon
Highlights: We undertook telephone and face-to-face interviews with 17 households during the winter period in England. Achieving warmth is seen as important due to concerns about health consequences. Households used different coping strategies to keep warm. Many residents saw coping strategies as unproblematic. These results have implications for organisations tackling fuel poverty. Abstract: Fuel poverty is a problem particularly associated with the lives and living conditions of older people, in part because of their vulnerability to health impacts. This article draws attention to the ways in which older people on low incomes cope with and adapt to problems of affording to keep warm at home. We present findings from interviews with 17 households during the winter of 2012–2013 in England. The importance of keeping warm was recognised across the interviews. Four particular categories of coping strategies were defined and used—responsively adjusting the length of time and parts of the home for which heating is kept on, using secondary heating sources; using additional layers that help to keep bodies warm; and adjusting daily routines. We found that it was rare for people themselves to problematize the ways in which they were coping day to day, they largely just saw this as what they did to get by and to control the size of their energy bills. Coping strategies raise questions about what are acceptable living conditions, how judgments are made and how assistance can be provided when householders do not themselves problematize their situation. Implications for action to tackle fuel poverty are considered.